27x-6=40x-16

Simple and best practice solution for 27x-6=40x-16 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 27x-6=40x-16 equation:



27x-6=40x-16
We move all terms to the left:
27x-6-(40x-16)=0
We get rid of parentheses
27x-40x+16-6=0
We add all the numbers together, and all the variables
-13x+10=0
We move all terms containing x to the left, all other terms to the right
-13x=-10
x=-10/-13
x=10/13

See similar equations:

| 8x2+10x=3=0 | | 125+30x=725 | | Y=27+10x | | 5x+25=3x+30 | | x2-15=1 | | 18=19-3x | | 7x−4=3 | | 6t+14-4t=-7 | | 11=2÷-4x | | X=2+20-3x | | 5x-24+9x-6=180 | | 16x2+20x=0 | | 5x-4=-3x+28 | | 1.2b+2.6=10.1-1.36 | | 5w+20=5 | | .15y=12 | | 6k-65=1 | | 139=39+(n-1)1 | | 3x-1÷2-2x-10÷2=7x-5÷5+0,1 | | m/3+2=13 | | b–9=7 | | 3(2x–5)=–16 | | 72+2w=132 | | 10x-3(x-6)=x30 | | 9/12=f/4 | | 46=9x | | 5x^2+36x+30=0 | | 35=8b+3 | | 530=12+(n-1)7 | | 6.3434=x10^-8 | | 7-6x+18+8x-40=3^2-x | | 3.75+3/8x=131/4 |

Equations solver categories